Instrumental deliveries and its outcome in tertiary care center - Ayesha Sultana, M.; Suprada, Kothapalli; Rao Bahadur, B.; Gangadhara Rao, K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Objective of the study was to determine the incidence and indication of assisted vaginal deliveries and to compare the fetal and maternal outcome of vacuum and forceps deliveries. Methods: This study done over a period of one and half year from March 2022 to August 2023 at NRI Medical College, Chinnakakani. Total number of vaginal deliveries are 1617, out of which 33 had a successful assisted vaginal delivery and studied in terms of maternal and fetal outcome. Verbal consent was taken, indication for instrumental application documented and pre requisites fulfilled before instrument application. Results: Out of 1617 vaginal deliveries in our institute, 33 cases successful underwent assisted vaginal deliveries in which 49% were vacuum assisted, 51% were forceps assisted deliveries. Most common indication for instrument application were fetal distress (51%), failure of maternal forces followed by maternal exhaustion (30%). We had 2nd degree perineal tear - 2 (11.76%), cervical tear - 1 (5.88%), PPH-1 (5.88%), 1- vaginal laceration (6.25%) as maternal complications. Out of 16 vacuum and 17 forceps deliveries, 5/16 (31.25%) and 8/17 (47.06%) were admitted in NICU respectively. Conclusions: In the present study showed that most common indication for assisted vaginal deliveries are fetal distress and maternal exhaustion. Maternal complications are seen more in forceps deliveries when compared to vaccum. There is no significant difference between vaccum and forceps deliveries in neonatal complications when compared.